Let's first try to rewrite the expression to see if we can write it in a fomr more familiar:
![\begin{gathered} x-√(10-3x)=0, \\ x=√(10-3x), \\ x^2=10-3x, \\ x^2+3x-10=0. \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9iao7l3p7cir53k4gt68939bo6hvikjfbl.png)
This is the same equation, but now we recognize a quadratic expression equal to 0. We can use the quadratic formula to find the solutions of this equation:
![x_(1,2)=(-3\pm√(3^2-4\cdot1\cdot(-10)))/(2\cdot1)](https://img.qammunity.org/2023/formulas/mathematics/college/xruos34xvh5k7oh2dvb57fqolf349et4e8.png)
And solve:
![\begin{gathered} x_(1,2)=(-3\pm√(9+40))/(2)=(-3\pm7)/(2) \\ x_1=(-3+7)/(2)=(4)/(2)=2 \\ x_2=(-3-7)/(2)=(-10)/(2)=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jynr8u4bl336hluy9oxqm233eafy0z9d2n.png)
Thus, the solution set of the equation is x = -5, x = 2